Pengaruh Kualitas Pelayanan dan Promosi Terhadap; Kepuasan Pelanggan, Perceived Value, dan Loyalitas Pelanggan Pengguna Shopee Food di Kota Yogyakarta - Ariyani, Riska; Albari, Albari (Jurnal Indonesia Sosial Sains, 2022)
The company that has recently emerged as a new competitor in the world of food delivery services is an E-commerce application called Shopee. Shopee introduces a food delivery service called Shopee Food which has the same function as other food delivery services. This study aims to examine the effect of service quality, promotion, perceived value, and customer satisfaction on customer loyalty of shopeeFood users in the city of Yogyakarta. The analytical method used is SEM which is processed using AMOS version 24.0. The population used in this study is the entire community of ShopeeFood users who are domiciled in the city of Yogyakarta. The sampling technique used in this study is convenience sampling. The results of this study indicate that of the 9 significant positive hypotheses consisting of 5 hypotheses and not significant consisting of 4 hypotheses. Service quality has no positive and significant effect on customer satisfaction. Service quality has a positive and significant effect on perceived value. Service quality has no positive and significant effect on customer loyalty. Promotion has a positive and significant effect on customer satisfaction. Promotion has a positive and significant effect on perceived value. Promotion has no positive and significant effect on customer loyalty. Perceived value has a positive and significant effect on customer satisfaction. Perceived value has no positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty.